Effects of Spectral Ranges on Growth and Yield in Vertical Hydroponic–Aeroponic Hybrid Grow Systems for Radishes and Turnips - Adia Shadd; Nima Asgari; Joshua M. Pearce (Foods)
As climate change destabilizes food crop production, there is a growing interest in controlled environment agriculture (CEA). Although light-emitting diodes (LED) have made CEA economically viable for some high-value crops when coupled to agrivoltaics (solar photovoltaics + agriculture), it has generally not been used for root vegetables. This is the first study to demonstrate that radishes and turnips could be grown in a reasonable period of eight weeks in an agrivoltaic agrotunnel using both lighting and grow walls optimized for lettuce growth. As reduction in LED energy use is important to minimize capital costs for solar energy, this study investigated three lighting treatments (red, white, and full-spectrum as control). The normalized yields (adjusted for total energy provided by each treatment) showed that both cultivars preferred red light, and harvested green leaves provided higher masses than the roots, although turnips appeared to be far more adaptable to vertical growth than radishes (>450% for roots and >50% for leaves per pot compared to radishes for the control treatment). The results show promise for providing true net-zero carbon emission root vegetables year-round with similar agrivoltaics-powered CEAs. Future work is needed with light intensity trials to optimize light recipes.